Surgical hip dislocation for removal of retained intra-articular bullets. Issue 10 (October 2016) - Maqungo, Sithombo; Hoppe, Sven; Kauta, Jimmy N.; McCollum, Graham A.; Laubscher, Maritz; Held, Michael; Keel, Marius J.B.
Abstract: Introduction: Surgical hip dislocation with trochanteric osteotomy was introduced for the treatment of femoroacetabular impingement and other intra-articular pathologies of the hip. We expanded the indications to include removal of retained bullets in the hip joint as an alternative to hip arthroscopy. Patients and Methods: We present a prospective case series of ten patients that were treated with a surgical hip dislocation for removal of retained bullets in the hip joint between January 2014 and October 2015 in a Level 1 trauma centre. The main outcome measurements were successful bullet removal, blood loss, surgical time and intraoperative complications. Results: There were 8 males and 2 females with a mean age of mean age 27.3 years (range 20–32). All patients had one whole retained bullet for removal (right side: 8; left side: 2). In all cases the bullet could be removed in its entirety. The average surgical time was 73 min (range 55–125) and the average blood loss 255 ml (range 200–420). Conclusions: Surgical hip dislocation provides an unlimited view of the acetabulum and femoral head and neck and it therefore allows for easy removal of retained bullets. Osteocartilaginous lesions and concomitant fractures of the femoral head can be simultaneously evaluated and treated.